KEMAMPUAN BERBAHASA ANAK DALAM BUKU HARIAN DITINJAU DARI KAJIAN MEMORI, PIKIRAN, DAN BAHASA - Rissa Beatrik S. (Center of Language and Cultural Studies, 2016)
This research describes contents of diary perceived from memory, mind, and language aspects. This research used content analysis design, focusing on analysis of students’ diaries. Five diaries obtained from students were used for analysis. Not all students memorized their daily events in a diary. The study revealed that flows of expression in the diary indicate flow of mind, expression and word choice. Memory shows sequence of events and chronological techniques of presentation. Thinking process captures how events and linkages between facts are integrated. Mind process shows critical thinking as reflected in the variety of word choices and sentence flows. Evidently, diaries support students’ writing quality.